IMPLEMENTATION OF INFORMATION SYSTEM FOR ADMINISTRATION AND GEOSPATIAL OF WERNAS VILLAGE IN SOUTH SORONG BASED ON WEBSITE AND ANDROID - Novandi Rezeki; Pailus, Muhammad (Jurusan Pendidikan Teknik Elektro, 2025)
This research aims to address the challenges of administration and natural resource management in Wernas Village, South Sorong, Southwest Papua, through the implementation of website-based administrative and geospatial information systems and Android applications. Wernas Village, which is currently still lagging behind in terms of technology, has great potential to develop a modern digital village, especially by utilizing abundant natural resources such as rivers. In order to achieve these objectives, this research uses mixed methods research that combines qualitative and quantitative approaches. The initial stage involved a preliminary study to analyze the needs and challenges of the village, followed by the design of an information system that included website design, Android application, and geospatial mapping.The prototype of the information system was then developed and tested in a limited environment in the village. Evaluation and refinement were carried out based on the results of the trial, with the aim of ensuring the information system was ready for full implementation. The targeted outputs of this research include the design of an information system prototype that is ready to be implemented, mapping of administrative needs and management of village natural resources, as well as improving the quality of public services and administrative efficiency. It is expected that the results of this research can make a significant contribution in improving the quality of life of the people of Wernas Village, accelerating inclusive and sustainable village development, and becoming an example for other villages in the South Sorong Regency area to adopt information technology to advance local development.